Effect of Industrial Pollution on the Spatial Variation of Surface Water Quality - Nasly, Mohamed Ali; Hossain, Mohamed Amjed; M. R., Islam; Sobahan, Md Abdus (American Journal of Environmental Science, 2013)
Surface water quality deterioration is the impact of anthropogenic activities at the study areas due to rapid industrialization. The study was done to know the spatial variation of the water quality of the Tunggak River and surrounding area because of industrial activities. In-situ parameters and ex-situ data of chemical, bio-chemical parameters and heavy metals were collected monthly to fulfill the objectives. The samples were collected from 10 selected stations and analyses were carried out using standard methods. Heavy metals were determined by using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). SPSS statistical software was used for data analysis. The results of the study revealed that industrial effluents were the major source of pollutants and caused of spatial variation among the stations. Less amount of Dissolved Oxygen (DO) and higher concentration of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), ammoniacal-nitrogen and heavy metals made the water un-usable except irrigation. Analyzed surface water was classified based on Department of Environment-Water Quality Index (DOEWQI) Malaysia and found that the maximum stations except lower and uppermost were in class IV (highly polluted). Pollution rate was higher in the middle stations due to large number of industries were located in the middle and they discharged all their effluents in the river stream. Due to tidal interference in the lower stream and minimum industry in the upper stream pollution was less in those stations.